2020
DOI: 10.1124/jpet.119.262865
|View full text |Cite
|
Sign up to set email alerts
|

Detailed In Vitro Pharmacological Characterization of the Clinically Viable Nociceptin/Orphanin FQ Peptide Receptor Antagonist BTRX-246040

Abstract: The peptide nociceptin/orphanin FQ (N/OFQ) is the natural ligand of the N/OFQ receptor (NOP) which is widely expressed in the central and peripheral nervous system. Selective NOP antagonists are worthy of testing as innovative drugs to treat depression, Parkinson's disease, and drug abuse. The aim of this study was to perform a detailed in vitro characterization of BTRX-246040 (also known as LY2940094, [2-[4-[(2-chloro-4,4-difluoro-spiro[5H-thieno[2,3-c]pyran-7,4'-piperidine]-1'-yl)methyl]-3-methylpyrazol-1-yl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
(44 reference statements)
0
9
1
1
Order By: Relevance
“…BTRX-246040 is a selective and potent NOP antagonist (Ferrari et al, 2020;Statnick et al, 2016) under development for the treatment of depression, eating disorders and alcohol abuse (Browne and Lucki, 2019;Witkin et al, 2019). In a small clinical proof of concept study performed in patients with major depressive disorders (MDD) BTRX-246040 (40 mg, p.o.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BTRX-246040 is a selective and potent NOP antagonist (Ferrari et al, 2020;Statnick et al, 2016) under development for the treatment of depression, eating disorders and alcohol abuse (Browne and Lucki, 2019;Witkin et al, 2019). In a small clinical proof of concept study performed in patients with major depressive disorders (MDD) BTRX-246040 (40 mg, p.o.)…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro pharmacological activity of BTRX-246040 has been recently characterized in detail and compared to those of the standard NOP antagonist SB-612111. BTRX-246040 is a pure and selective antagonist at human recombinant and murine native NOP receptors displaying 3 -10 fold higher potency than the standard antagonist SB-612111 (Ferrari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained using compound 40 and 43 as NOP agonists; the p A 2 values of SB-612111 calculated from these experiments were 7.95 (CL 95% 7.43–8.47) and 7.77 (CL 95% 7.32–8.21), respectively (see Figure S1 of the Supporting Information). Thus, SB-612111 competitively antagonized the effects of N/OFQ, , N/OFQ(1–13)-NH 2 , and compounds 40 and 43 , showing similar p A 2 values. This demonstrated that similar to N/OFQ and N/OFQ(1–13)-NH 2 , compounds 40 and 43 activate the NOP receptor by interacting with the orthosteric binding pocket that has been described at the atomic level in previous NOP/C-24 and NOP/SB-612111 crystal structure studies.…”
Section: Resultsmentioning
confidence: 99%
“…При этом не было отмечено положительного эффекта препарата на такие показатели нарушения сна как ранняя бессонница (трудности при засыпании), средняя (многократные пробуждения в течение ночи) и поздняя бессонница (ранние пробуждения) [79]. В настоящее время свойства LY2940094 (BTRX-246040) активно изучают в экспериментах in vivo и in vitro [81].…”
Section: тревожность: анксиолитический или анксиогенный эффекты стимуunclassified